2016
DOI: 10.1002/jssc.201600941
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted supramolecular‐solvent‐based microextraction combined with high‐performance liquid chromatography for the analysis of chlorophenols in environmental water samples

Abstract: Ultrasound-assisted supramolecular-solvent-based microextraction combined with high-performance liquid chromatography for the analysis of chlorophenols in environmental water samplesAn efficient, inexpensive and environmentally benign ultrasound-assisted supramolecularsolvent-based microextraction technique combined with high-performance liquid chromatography was used for the determination of chlorophenols in environmental water samples. Different factors such as amount of decanoic acid, volume of tetrahydrofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They can represent serious health hazards due to their moderate bioaccumulation and high toxicity, which increase with the increment of chlorination . Once CPs enter the food chain, human health is threatened by biological concentration, causing metabolic disorders, physiological imbalance, and cancer . The European community has stipulated the maximum allowed phenol concentration in drinking water to be 0.5 μg/L .…”
Section: Introductionmentioning
confidence: 99%
“…They can represent serious health hazards due to their moderate bioaccumulation and high toxicity, which increase with the increment of chlorination . Once CPs enter the food chain, human health is threatened by biological concentration, causing metabolic disorders, physiological imbalance, and cancer . The European community has stipulated the maximum allowed phenol concentration in drinking water to be 0.5 μg/L .…”
Section: Introductionmentioning
confidence: 99%
“…Anderson's group 45,48−50 48 Regarding SUPRASs, they emerge from amphiphilic solutions through two concurrent self-assembly processes taking place at molecular and nano scales, resulting in a nanostructured liquid that is immiscible with water. It can be directly used as a solvent for extracting components, as Karimiyan et al 51 reported, or taking advantage of their high functionality, as Salatti-Dorado et al proposed. 52 Concretely, Karimiyan's group has proposed the use of supramolecularsolvent (based on reverse micelles of decanoic acid in tetrahydrofuran) for the ultrasound-assisted (UA)-LPME combined with HPLC for the analysis of chlorophenols in environmental water samples.…”
Section: ■ Green Sample Preparationmentioning
confidence: 99%
“…It should be remarked that the process is straightforward and quick, requiring no cleanup of extracts or solvent evaporation, being both cost-effective and environmentally friendly. 51 In contrast, Salatti-Dorado's group proposed the use of SUPRAS as a restricted access volatile supramolecular solvent for the LC-MS/MS assay of bisphenol A in urine. In this case, the SUPRASs role is based on the removal of ionization suppression by eliminating proteins and phospholipids from biological samples by simple flocculation.…”
Section: ■ Green Sample Preparationmentioning
confidence: 99%
“…CE methods especially capillary zone electrophoresis (CZE) have found their place in modern separation science as versatile and efficient techniques for the analysis of a wide range of analytes in a variety of sample matrices, such as the analytes of organic compound [22], inorganic ions [23,24], proteins [25], and vitamins [26], in a series of samples. CE based methods have been described in literatures for the quantification of chlorophenols in some matrices [27][28][29]. However, only one research has been reported regarding the determination of HCP in water samples by CE with electrochemical detection [30].…”
Section: Introductionmentioning
confidence: 99%